Резонансні процеси в пускових режимах синхронних двигунів з конденсаторами в колі обмотки збудження - Маляр, М.И.; Мадай, В.С.; Кенс, І.Р. (Електротехніка і електромеханіка, 2017)
Розглядається проблема появи резонансу під час асинхронного пуску явнополюсних синхронних двигунів, в яких для
підвищення електромагнітного моменту в коло обмотки збудження увімкнено конденсатори. Для розрахунку пускових статичних характеристик та дослідження впливу величини ємності конденсаторів на перебіг пуску двигуна, зокрема появу резонансу, використовується математична модель синхронного двигуна явнополюсної конструкції високого рівня адекватності, в якій враховується насичення магнітопроводу. Асинхронний режим описується системою
диференціальних рівнянь електричної рівноваги, записаної в ортогональних координатних осях з урахуванням наявності конденсаторів в обмотці збудження. Електромагнітні параметри контурів визначаються на основі розрахунку
розгалуженої заступної схеми магнітного кола двигуна. В основу розробленого алгоритму покладено заснований на
апроксимації кубічними сплайнами проекційний метод розв’язування крайових задач розрахунку усталених періодичних режимів і диференціальний метод розрахунку статичних характеристик. Рассматривается проблема возникновения резонанса во время асинхронного пуска явнополюсных синхронных двигателей, в которых для повышения электромагнитного момента в цепь обмотки возбуждения включены конденсаторы. Для расчета пусковых статических характеристик и исследования влияния величины емкости конденсаторов на
протекание пуска двигателя, в частности появления резонанса, используется математическая модель синхронного
двигателя явнополюсной конструкции высокого уровня адекватности, в которой учитывается насыщение магнитопровода. Асинхронный режим описывается системой дифференциальных уравнений электрического равновесия, составленной в ортогональных координатных осях с учетом наличия конденсаторов в обмотке возбуждения. Электромагнитные параметры контуров определяются путем расчета разветвленной схемы замещения магнитной цепи
двигателя. В основу разработанного алгоритма положен основанный на аппроксимации кубическими сплайнами проекционный метод решения краевых задач расчета установившихся периодических режимов и дифференциальный
метод расчета статических характеристик Purpose. Development of a mathematical model that enables to
detect resonance modes during asynchronous startup of salientpole synchronous motors, in which capacitors are switched on
to increase the electromagnetic moment in the circuit of the
excitation winding. Methodology. The asynchronous mode is
described by a system of differential equations of the electric
equilibrium of motor circuits written in orthogonal coordinate
axes. The basis of the developed algorithm is the mathematical
model of the high-level adequacy motor and the projection
method for solving the boundary value problem for the equations of the electric equilibrium of the circuits written in orthogonal coordinate axes, taking into account the presence of
capacitors in the excitation winding. The coefficients of differential equations are the differential inductances of the motor circuits, which are determined on the basis of the calculation of its
magnetic circuit. As a result of the asymmetry of the rotor windings in the asynchronous mode, the current coupling and currents change according to the periodic law. The problem of its
definition is solved as a boundary one. Results. A mathematical
model for studying the asynchronous characteristics of synchronous motors with capacitors in an excitation winding is developed, by means of which it is possible to investigate the influence of the size of the capacity on the motor's starting properties
and the resonance processes which may arise in this case. Scientific novelty. The developed method of mathematical modeling is based on a fundamentally new mathematical basis for the
calculation of stationary dynamic modes of nonlinear electromagnetic circuits, which enables to obtain periodic coordinate
dependencies, without resorting to the calculation of the transients. The basis of the developed algorithm is based on the
approximation of state variables by cubic splines, the projection
method of decomposition for the boundary value problems of the
calculation of the established periodic modes and the differential method of calculating static characteristics. Practical value.
Using the developed algorithm of calculation it is possible to
determine the required capacitances of the capacitors in the
excitation winding to start the synchronous motor and to investigate the possibility of occurrence of the resonance at startup
with the selected capacitance value of the capacitors by calculating the static characteristics as a sequence of asynchronous
modes